Refugee Inflow and Islamophobia in Germany Post 2015: A Descriptive Analysis by Using Anti-Muslim Hate-Crime Indicators - Anantakupa, Azhar Gusti; Farzana, Anindita Rifa; Krym, Gabit (Indonesian Center for Religion and Society Studies (InTReSt), 2025)
Existing studies on post-2015 backlash in Germany often rely on broad xenophobia indicators, which can conflate Islamophobia with general anti-immigrant hostility. This study documents whether anti Muslim hate crime shows a distinct post-2017 trajectory using the official ‘islamfeindlich’ category. Using a qualitative-descriptive design grounded in the qualitative description approach, the study combines descriptive trend analysis of BKA/PMK “islamfeindlich” data for 2017–2024 with narrative synthesis of OSCE/ODIHR hate crime reports, the UEM expert report, and comparative research on the 2015/16 inflow and social cohesion. Guided by Group Threat Theory and the Islamophobia framework, the analysis shows that official “islamfeindlich” statistics reveal a persistently high and recently intensifying pattern of anti-Muslim incidents from 2017 to 2024, indicating that the short-term anti-immigrant backlash triggered by the 2015–2016 refugee inflow indicates a sustained pattern of religion-specific hostility directed at Muslims. Implications: The study highlights the need for precise outcome measures and supports policy interventions such as routine protection of mosques, targeted anti-bias and media literacy programs, and improved reporting mechanisms that link administrative and civil society monitoring.